Research Notes Iss. 4, 2017. - Various authors ((The University of the West Indies, Faculty of Humanities and Education, Dept. of Modern Languages and Linguistics, 2017), 2017)
DMLL Research Notes Issue No. 4 features the work of Prof. Elizabeth Walcott-Hackshaw, academic and writer (novels and short stories). Prof Walcott-Hackshawgives us insight into her creative writing process, and a peek into her new collection of short stories.